**Hello Aspirants.** Welcome to Online Quantitative Aptitude Section with explanation in AffairsCloud.com. Here we are creating question sample in **Ages **which is common for all competitive exams. We have included Some questions that are repeatedly asked in bank exams !!!

**This year, the sum of ages of the Suresh’s family members is 78. Currently, there are 4 members namely viz Suresh, Rita, Deepa and Tarun. Suresh is 4 years older than Rita. Deepa is two years older than Tarun. If Suresh is 7 times as old as Tarun, how old is Deepa?**

A. 5

B. 7

C. 8

D. 9

E. 6

Answer –**B. 7**

**Explanation :**

S+R+D+T = 78 – (i)

S = R + 4 – (ii)

D = T + 2 – (iii)

S = 7T – (iv)

7T = R+4

R= 7T – 4

h+w+d+s = 78 – (i)

7T+7T-4+T+2+T = 78

16T = 80

T = 5

d = T+2 = 5+2 = 7**Three years from now, Deepa will be three times as old as Emma and Emma will be six years younger than Femina. If Deepa’s age is three years less than twice Femina’s age, how old is Femina?**

A. 9

B. 15

C. 21

D. 27

E. 33

Answer –**A. 9**

**Explanation :**

D+3=3(E+3)

E+3=(F+3)-6

D=2F-3.

E+3=F-3 or E=F-6.

D+3=3(F-6+3)

D+3=3F-9

D=3F-12.

now, we have D=2F-3.

2F-3=3F-12

9=F**Ravi is now 4 years older than Emma and half of that amount older than Ishu. If in 2 years, Ravi will be twice as old as Emma, then in 2 years what would be Ravi’s age multiplied by Ishu’s age?**

A. 68

B. 28

C. 48

D. 50

E. 52

Answer –**C. 48**

**Explanation :**

Ravi – x + 4

Emma – x

Ishu – x + 2

(Ravi 4 years older than Emma & 2 years older than Ishu)

Ages after 2 yrs

Ravi – x + 6

Emma – x + 2

Ishu – x + 4

x+6 = 2(x + 2)

x = 2

Ravi * Ishu = 8 * 6 = 48**Jack is now twice as old as Femina, who is two years older than Suresh. Four years ago, Jack was four times as old as Suresh. How old is Jack now?**

A. 18

B. 12

C. 16

D. 20

E. 24

Answer –**D. 20**

**Explanation :**

j=2f – (i)

f=s+2.-.(ii)

four years ago

j-4=4(s-4)

putting (ii) in (iii)

we get j-4 =4(f-2-4)

sub (i) in above equation we get

j-4=4(j/2-6) =>j=20**James is now 12 years younger than Mahesh. If 9 years from now Mahesh will be twice as old as James, how old will James be in 4 years?**

A. 3

B. 7

C. 5

D. 9

E. 8

Answer –**B. 130**

**Explanation :**

James =x years, Mahesh = x+12 years

9 from now,

2(x+9)=x+21

2x+18=x+21

x=3

x+4 =7 years**Ravi has three children: two daughters and one son. All were born on the same date in different years. The sum of the ages of the two daughters today is smaller than the age of the son today, but a year from now the sum of the ages of the daughters will equal the age of the son. Three years from today, the difference between the age of the son and the combined ages of the daughters will be**

A. 1

B. 2

C. 3

D. –2

E. –1

Answer –**D. –2**

**Explanation:**

one year from now, D+d=s

two years after that, D+2+d+2=s+2

D+d-s=2-4=-2**Leena’s age is 5 years more than twice Gayathri’s age. Vijay’s age is 13 years less than 10 times Gayathri’s age. If Vijay is 3 times as old as Leena, how old is Leena?**

A. 17

B. 16

C. 12

D. 14

E. 19

Answer –**E. 19**

**Explanation :**

given l = 2g+5

v = 10g-13

v=3l

f rom v=3l => 10g-13 = 6g+15

g = 7

l= 2g+5 = 19**8 years ago, Geeta was half as old as Saina. Saina is now 20 years older than Geeta. How old will Geeta be in 10 years?**

A. 45

B. 40

C. 35

D. 38

E. None of the Above

Answer –**D. 38**

**Explanation :**

Saina is now 20 years older than Geeta –> S=G+20 –> Saina 8 years ago was G+20-8=G+12 years old.

(G-8)*2=G+12 –> G=28. 28+10=38 years.**Lilly is 5 years older than Martin, and Catherine is twice as old as Lilly. If the sum of their ages is 95, how old is Lilly?**

A. 26

B. 27

C. 28

D. 25

E. None of these

Answer –**D. 25**

**Explanation :**

L=5+M and C=2L and C+M+L=95 => 4L=100 => L=25**Arun will be half as old as Lilly in 3 years. Arun will also be one-third as old as James in 5 years. If James is 15 years older than Lilly, how old is Arun?**

A. 6

B. 8

C. 9

D. 5

E. 4

Answer –**B. 8**

**Explanation :**

let age of Arun =x, Lilly =y James = z

(x+3) =1/2 *(y+3) so we have 2x-y =-3 -(1)

(x+5) =1/3 * (z+5) ; => 3x-z=-10 -(2)

From (1)&(2) we get, x+y-z =-7 -(3)

we have z =15+y – (4)

from equation 3 and 4 we get x=8

**AffairsCloud Recommends Oliveboard Mock Test**

**AffairsCloud Ebook - Support Us to Grow**

**Govt Jobs by Category**

**Bank Jobs Notification**